2019
DOI: 10.1002/ijc.32836
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of serum bone resorption markers for predicting clinical outcomes after use of bone modifying agents in metastatic bone tumors: A prospective cohort study

Abstract: Bone modifying agents (BMAs) have become a standard treatment to prevent skeletal-related events (SREs) in bone metastases (BMs). The aim of our study is to determine the clinical value of serum bone resorption markers for predicting clinical outcomes after using BMAs in patients with BM. Patients were enrolled between May 2013 and October 2017 at the Nagoya University Hospital, Japan. We prospectively observed changes in pyridinoline cross-linked carboxyterminal telopeptide of type I collagen (ICTP) and tartr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Tumor cells will degrade the bad bone apoptotic component, osteoclasts will be activated, osteolysis will be seen, and bone metastases will damage bone, resulting in an increase in blood calcium levels [ 24 ]. The study evaluated the therapeutic effectiveness of bisphosphonate medicines in eligible individuals with lung cancer and bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells will degrade the bad bone apoptotic component, osteoclasts will be activated, osteolysis will be seen, and bone metastases will damage bone, resulting in an increase in blood calcium levels [ 24 ]. The study evaluated the therapeutic effectiveness of bisphosphonate medicines in eligible individuals with lung cancer and bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the very strong correlation between osteolysis, as detected by circulating concentration of TRACP5b and IL-8 in BM patients. TRACP5b is a specific index of bone resorption, and an accurate marker of OC number since it is released from OC into the blood circulation, together with matrix degradation products, during the bone resorption process through the basolateral membrane (Avnet et al, 2008;Savarino et al, 2010;Urakawa et al, 2020). However, in these patients, we could not directly prove that the release of these inflammatory mediators is derived from the cancer-induced bone lesion or from intratumoral acidosis.…”
Section: Discussionmentioning
confidence: 82%
“…In this phase III trial, the surrogate endpoint of Week 13 uNTx/Cr was used as the primary endpoint, which was widely used as an indicator of bone resorption [22,27]. The uNTx/Cr serves as a highly speci c biomarker for bone osteolysis and proves to be a valuable predictor for the treatment of BM [27][28][29][30]. Regulatory guidelines from the NMPA, the U.S. Food and Drug Administration (FDA), and the European Medicines Agency (EMA) support the use of biomarkers as primary endpoints in biosimilar clinical trials against their reference products [31 -33].…”
Section: Discussionmentioning
confidence: 99%